CUSTOMER ANXIETY AFTER COVID-19 AND ITS IMPACT TO THE BEHAVIORAL INTENTION AT HYPERMARKET - Fauziah, Fenty; Nardi, Nardi; Fitriansyah, Fitriansyah; Zien , Rushami; Nurfadillah, Mursidah (TRIKONOMIKA, 2024)
The COVID-19 pandemic has significantly impacted the modern retail sector, particularly hypermarkets in East Kalimantan, influencing consumer behavior by creating anxiety and promoting both hedonic and utilitarian shopping behaviors. This study examines how attitudes toward behavior mediate the relationship between anxiety, utilitarian value, hedonic value, and behavioral intention among hypermarket consumers post-pandemic. The study addresses theoretical and empirical inconsistencies in these relationships. Involving 160 participants selected through systematic random sampling, data were analyzed using Partial Least Squares (PLS) with Smart PLS 3.0. Seven hypotheses were tested. Findings indicate that only utilitarian value and attitude toward behavior significantly affect behavioral intention. Both hedonic and utilitarian values predict attitudes toward behavior, while anxiety has a negative and insignificant effect on both behavioral intention and attitudes. Post-pandemic, consumers are no longer anxious about shopping at hypermarkets, suggesting a need for improved promotions and services in hypermarkets.